ЯЗЫКОВЫЕ СРЕДСТВА КАРАКАЛПАКСКОГО ЯЗЫКА ДЛЯ ПЕРЕДАЧИ ЛОКАЛЬНОГО ЗНАЧЕНИЯ РУССКИХ ПРЕДЛОГОВ «ИЗ-ЗА» И «ИЗ-ПОД» - Хошанов, Б.Х. (SCIENCE and SOCIETY, 2017)
The article deals with linguistic means of the Karakalpak language to transfer the local meaning of the Russian prepositions as “because of and “from under”.